Feminism, femininity and motherhood in post-World War II New Zealand : A thesis submitted for the degree of Master of Arts in history at Massey University - Knox, Heather (Massey University, 1995)
Hanging between the turmoil of global war and the social challenges and changes of later decades, the 1950s tends to be remembered as a time of social order, consensus and security. As a result, researchers often view these years as ones of stagnation for New Zealand women; a time when the stable nuclear family ruled supreme, when men's and women's roles were clearly delineated and little action was taken towards challenging them. However recent expansions of our perceptions of political activism have suggested otherwise. Helen May, for example, has taken a wider view of women's politics that incorporates domestic-based and non-controversial and argued that the apparent tranquility of the 1950s covered elements of conflict and contradiction. She and other historians maintain that women, while conforming to dominant expectations of their role, were also actively negotiating change in their lives. This thesis aims to investigate the extent to which three New Zealand women's groups centred on mothering, Parents' Centre, Play Centre and the Plunket Society, served as vehicles of these hopes for change. To this end, the relative degrees of progressive "feminist" and traditionalist "maternalist" elements within the organistions' philosophy and process are analysed. It is argued that the nature of each organisation is distinctive, with each showing a particular balance of feminist and maternalist characteristics. Together, the three organisations represent a continuum of women's political activities and illustrate the diversity of women's politics both within a particular time and within individual groups.
Keywords: Motherhood; Feminism; New Zealand